2007
DOI: 10.1104/pp.107.105676
|View full text |Cite
|
Sign up to set email alerts
|

The ArabidopsisDESPERADO/AtWBC11Transporter Is Required for Cutin and Wax Secretion

Abstract: The cuticle fulfills multiple roles in the plant life cycle, including protection from environmental stresses and the regulation of organ fusion. It is largely composed of cutin, which consists of C 16-18 fatty acids. While cutin composition and biosynthesis have been studied, the export of cutin monomers out of the epidermis has remained elusive. Here, we show that DESPERADO (AtWBC11) (abbreviated DSO), encoding a plasma membrane-localized ATP-binding cassette transporter, is required for cutin transport to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
264
3
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(286 citation statements)
references
References 59 publications
15
264
3
4
Order By: Relevance
“…The results indicated that, instead of an overexpression, we obtained cosuppression in the transgenic plants. This has been reported previously for AtABCG11, where overexpression of this gene resulted in a cosuppression (Panikashvili et al, 2007(Panikashvili et al, , 2010.…”
Section: Map-based Cloning Of Osabcg26mentioning
confidence: 55%
See 2 more Smart Citations
“…The results indicated that, instead of an overexpression, we obtained cosuppression in the transgenic plants. This has been reported previously for AtABCG11, where overexpression of this gene resulted in a cosuppression (Panikashvili et al, 2007(Panikashvili et al, , 2010.…”
Section: Map-based Cloning Of Osabcg26mentioning
confidence: 55%
“…Some plant ABCG proteins have been reported to contribute to the synthesis of extracellular barriers. In Arabidopsis, ABCG11 (Cuticular Defect and Organ Fusion1/DESPERADO/White-Brown Complex11; Bird et al, 2007;Panikashvili et al, 2007Panikashvili et al, , 2010, ABCG12 (Eceriferum5/WBC12; Pighin et al, 2004), ABCG13 (Panikashvili et al, 2010), ABCG29 (Alejandro et al, 2012), ABCG32 (Bessire et al, 2011), and ABCG26 (WBC27; Xu et al, 2010;Quilichini et al, 2010Quilichini et al, , 2014Choi et al, 2011;Dou et al, 2011) have been shown to be involved in transport of lipidic compounds. Notably, it has been reported that these ABCG proteins have a broad substrates spectrum (for example, ABCG11 transports both cutin and wax monomers, and ABCG13 and ABCG32 mainly transport cutin monomers, whereas ABCG12 mainly transports wax precursors, and ABCG29 mainly transports monolignol).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cuticles, the hydrophobic, waxy structures produced by the epidermal cells in most land plants, play an important role in plant development and in the tolerance to environmental stresses. The constituents of the cuticle include fatty acids, esters, alcohols, aldehydes, ketones, and alkanes (Kunst and Samuels, 2003;Panikashvili et al, 2007). Defects in fatty acid metabolism or transport can also cause anther degeneration.…”
mentioning
confidence: 99%
“…Panikasvili and Aharoni (O4) showed the involvement of an ABC transporter, and presented their first results of an exhaustive study concerning ABC transporters [40].…”
Section: Sphingolipids Sterols Isoprenoidsmentioning
confidence: 99%